Introduction to quantum information science - Vedral, Vlatko (Oxford graduate texts, 2010)
In addition to treating quantum communication, entanglement and algorithms, this book also addresses a number of miscellaneous topics, such as Maxwell's demon, Landauer's erasure, the Bekenstein bound and Caratheodory's treatment of the Second law of thermodyanmics.